Influência dos treinamentos aeróbico, resistido e combinado sobre as propriedades físicas e biomecânicas ósseas de ratos obesos com diabetes melittus tipo 2 experimental - Silva, Karina Ana da (2016)
Background: Obesity is a condition characterized by an excessive amount of fat and has been considered an important factor for T2DM (type II Diabetes Mellitus) development. The T2DM, a state of hyperglycemia and insulin resistance, is often associated to an increased risk of bone fracture. Research question: investigate if three different physical exercise protocols could protect the bone tissue in obese rats with experimental type 2 diabetes mellitus. Type of study: Randomized controlled study Methods: Eighty male Wistar rats (45 days age ay beginning of the experiment) were used. The animals were randomly distributed into 2 groups: control rats fed with standard diet (n=40) and rats fed palatable hyperlipidic diet. After 4 weeks of treatment to induce diabetes, high-fat diet rats received, with previous fasting, a dose of Streptozotocin 35 mg/kg body weight, intraperitoneally. Control rats received, with previous fasting, a dose of citrate buffer solution (1ml/kg) intraperitoneally. The animals were assigned to one of the ten groups (n=10 per group): non-diabetic sedentary (CSS); non-diabetic resistance training (TRS); nondiabetic aerobic training (TAS); non-diabetic combined training (TCS), Sedentary diabetic (CSD); resistance training diabetic (TRD); aerobic training diabetic (TAD); combined training diabetic (TCD). The training procedures were realized after induction of diabetes, during 10 weeks, 3 days/week. Results: Body mass of diabetic groups was lower when compared to those groups without diabetes, in spite of greater calories consumed. Diabetic groups showed lower bone mineral content values when compared non-diabetic group. The bone mineral density was lower in TRD group. The maximal load and stiffness in diabetic groups was lower than their respective groups without diabetes. Groups with experimental diabetes present lower valuer for MMP-2 activity compared non-diabetic groups. Diabetes seems to induce reduced bone quality and the resistance training demonstrated protect the bone from it. Conclusion: Experimental diabetes mellitus type 2 affects the biomechanical properties of femurs of Wistar rats and the resistance training improve such effects.